Perinodal slow potential as a local guide for transcatheter radiofrequency ablation of atrioventricular nodal reentrant tachycardia: therapeutic efficacy and electrophysiological mechanisms of success. Issue 3 (September 1995) - Lin, J. L.; Lin, F. Y.; Lo, H. M.; Tseng, C. D.; Cheng, T. F.; Chen, J. J.; Tseng, Y. Z.; Lien, W. P.
Abstract : BACKGROUND–A specific local indicator in the Koch's triangle could be critical to the complication-free treatment of atrioventricular nodal reentrant tachycardia by transcatheter radiofrequency ablation. Recording of perinodal slow potential reflects a slow conduction area, and probably indicates the location of the slow pathway component of the circuit. Specific ablation of the slow pathway would carry the least risk of atrioventricular block. METHOD AND RESULTS–Guided by the mapped perinodal slow potential, atrioventricular nodal reentrant tachycardia was successfully eliminated in all of 55 consecutive patients in one session. Fifty two patients (94.5%) had confirmed slow potential at the final success sites. Despite the good result, the underlying electrophysiological mechanisms of early success from slow-potential-guiding catheter ablation were heterogeneous: selective slow pathway eradication in 31 patients (56.4%, group A), selective slow pathway modification in 18 patients (32.7%, group B), inadvertent fast pathway damage in six patients (10.9%, group C). Group B patients had the preservation of dual atrioventricular nodal pathways, adequate atrio-Hisian delay, fast pathway facilitation, and a higher frequency of inducible, single non-conducted nodal echo (15/18, 83.3% v 6/31, 19.4% in group A, P << 0.001). The upper communicating path of the circuit was implicated as another site of radiofrequency destruction. Three recurrences were documented in follow up study. However, reablation by the same approach caused complete atrioventricular block in one patient (1.7%, 1/58 procedures). None of the local characteristics of ablation sites was an independent predictor of procedure outcome. CONCLUSIONS–Perinodal slow potential is not a specific slow pathway indicator in transcatheter radiofrequency ablation of atrioventricular nodal reentrant tachycardia. Multiple strategic sites of the reentry circuit may be damaged through similar local signals.